2014
DOI: 10.1063/1.4863143
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced x-ray emissions from Au-Gd mixture targets ablated by a high-power nanosecond laser

Abstract: As an important x-ray source, enhancement of x-ray emissions from laser-produced plasmas is imperative for various applications. High-Z Au-Gd mixture targets are proposed to enhance the laser to x-ray conversion efficiency compared to pure Au target. In the experiments, a 1 ns frequency-tripled (351 nm wavelength) laser light was used to obtain an intensity of 3×1014 W/cm2 on the targets. The x-ray spectra, total absolute x-ray emissions of all space, M-band fraction and backscattering from pure Au and Au-Gd m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The experiments were conducted on the Shenguang-II laser facility. A schematic of the experimental layout and plot of the laser temporal profile-identical with those of [30,35]-are shown in figure 1. The plasma is produced by irradiating the solid-density gold planar targets or the Au foam planar targets normally with the intense frequency-tripled (351 nm wavelength) beam nine laser, which is smoothed by the lens array (LA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments were conducted on the Shenguang-II laser facility. A schematic of the experimental layout and plot of the laser temporal profile-identical with those of [30,35]-are shown in figure 1. The plasma is produced by irradiating the solid-density gold planar targets or the Au foam planar targets normally with the intense frequency-tripled (351 nm wavelength) beam nine laser, which is smoothed by the lens array (LA).…”
Section: Methodsmentioning
confidence: 99%
“…High-Z foam targets are hence predicted to be very favorable for indirect ICF, with good conversion efficiency and improved symmetry control [28]. Several other targets, including high-Z mixture target [29,30], even high-Z mixture foam target [31], double-foil gold target [32], and so on [33], have also been put forward as high brightness x-ray sources.…”
Section: Nuclear Fusionmentioning
confidence: 99%
“…Various efforts are put forward to enhance the conversion efficiency through an appropriate choice of laser and target parameters. In the context of indirect drive ICF scheme, use of short wavelength laser [10][11][12][13][14][15] , high-Z targets 16,17 , long pulse duration 18,19 , mixture/cocktail [20][21][22][23][24][25] are proposed to enhance the conversion efficiency in the range of multi-eV to multi-keV. Recently, various other methods like CH foam coated gold targets 26 , low density high-Z foam target 27,28 , double foil (DF) target 29 , counter propagating (CP) laser beams irradiation 30 , sandwiched target [31][32][33] , multi-layer target 34 and DF target irradiated with CP laser beams 35 are considered to increase the conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that mixed, multilayer and surface-structured targets can be used to increase the laser energy absorption. For example, high-Z mixture targets [27], porous or foamlike targets [28][29][30][31], multilayer targets [32,33], nanowire arrays [34][35][36], gratings [37][38][39] and doped aerogel targets [40,41]. In this context, investigations conducted on low density structured materials have shown that foam-attached targets or multilayer targets consisting in a solid substrate coated with a low-density layer offer significant enhancement of laser energy absorption and electron heating leading to higher conversion efficiency of laser energy into x-rays or energetic particles [29-31, 42, 43].…”
Section: Introductionmentioning
confidence: 99%